2002
DOI: 10.1046/j.1525-139x.2002.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated Peritoneal Dialysis Symposium: Intra‐abdominal Pressure, Peritoneal Dialysis Exchange Volume, and Tolerance in APD

Abstract: Automated peritoneal dialysis (APD) is increasingly popular compared to continuous ambulatory peritoneal dialysis (CAPD). It not only can provide more solute clearance and ultrafiltration than its CAPD counterpart, but it is conducive to a more convenient lifestyle as well. Using relatively smaller-volume daytime dwells, with the use of larger-volume exchanges while the patient is recumbent during the night, is an attractive approach. Advantages of supine exchanges include greater small molecule clearances for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Although our results demonstrate an association between DV/FV and clinical severity of the overfill event, our findings also illustrate the variability and unpredictability of clinical outcomes associated with a given amount of increase in IPV, as illustrated by relatively minor complications in 2 patients and death in 2 other patients that all experienced a similar increase in IPV. The findings in the current report substantiate other published studies that note variability in the relationship between the onset of noninfectious complications and degree of IPV excess or increase in intraperitoneal pressure (IPP) among adult and pediatric PD patients (6-8). It should be noted that an association between an increase in IPV and clinical outcomes in this observational study does not imply causality.…”
Section: Discussionsupporting
confidence: 90%
“…Although our results demonstrate an association between DV/FV and clinical severity of the overfill event, our findings also illustrate the variability and unpredictability of clinical outcomes associated with a given amount of increase in IPV, as illustrated by relatively minor complications in 2 patients and death in 2 other patients that all experienced a similar increase in IPV. The findings in the current report substantiate other published studies that note variability in the relationship between the onset of noninfectious complications and degree of IPV excess or increase in intraperitoneal pressure (IPP) among adult and pediatric PD patients (6-8). It should be noted that an association between an increase in IPV and clinical outcomes in this observational study does not imply causality.…”
Section: Discussionsupporting
confidence: 90%
“…Especially in PD patients that underwent abdominal surgery or those with severe heart failure, abdominal distention might induce hemodynamic changes and ischemia with a subsequent upregulation of growth factors, which in turn might contribute to the chronic degradation of the PM [55,56]. In automated PD, the intraperitoneal pressure per volume of dialysate is lower compared to CAPD [57]. However, to-date, no association has been found between different PD modalities and OS status or degree of PM injury.…”
Section: Other Pd-specific Factors Related With Osmentioning
confidence: 99%
“…With regard to PD options, APD may be offered to the patient. Automated peritoneal dialysis, performed in the supine position, decreases intra-abdominal pressure compared to CAPD (5). Often, minimal to no PD fluid remains in the abdomen during the daytime when the patient is in the erect position.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have suggested that patients' survival and yearly incidence of infectious complications are similar between the two modalities (1-3). However, some recent studies have suggested an improvement in technical survival in patients receiving APD compared to CAPD (4,5). Based on these cross-sectional studies as well as clinical experience, it is clear that either modality is suitable for stable patients with end-stage renal disease (ESRD) in the chronic ambulatory setting.…”
Section: Disclosuresmentioning
confidence: 99%